Trends in Canadian ophthalmology residency match outcomes - Mah, Jeffrey; Kherani, Irfan; Hurley, Bernard (Canadian Medical Education Journal, 2020)
Background: To date, there exists no formal assessment of the competitiveness of the residency match for Canadian ophthalmology programs. The primary objective of this study was to use Canadian Resident Matching Service (CaRMS) data to describe trends in the number of positions, number of applicants and level of competition for the Canadian ophthalmology match. Methods: The number of positions and the number of applicants for each ophthalmology program were received from CaRMS for each cycle of the match from 2006-2017. The level of competition was calculated by dividing total number of applicants by the total number of positions in any given year. Results: The level of competition was consistently high with a median number of 2.0 applicants per anglophone Canadian Medical Graduate (CMG) position, 2.6 applicants per francophone CMG position and 32.5 applicants per International Medical Graduate (IMG) position. Over the study period, the level of competition decreased for francophone CMG and IMG positions and did not change for anglophone CMG positions. Conclusion: Consistently there are a greater number of applicants than positions for Canadian ophthalmology residency programs and therefore CMG applicants should be encouraged to apply to more than one discipline. The trends in the number of residency positions can be used to update supply projections for ophthalmologists and guide human resource planning.